Osteogenic Potential of Human Oral‐Periosteal Cells (PCs) Isolated From Different Oral Origin: An In Vitro Study. Issue 3 (March 2016) - Ceccarelli, Gabriele; Graziano, Antonio; Benedetti, Laura; Imbriani, Marcello; Romano, Federica; Ferrarotti, Francesco; Aimetti, Mario; Cusella De Angelis, Gabriella M.
Abstract : The periosteum is a specialized connective tissue containing multipotent stem cells capable of bone formation. In this study, we aimed at demonstrating that human oral periosteal cells derived from three different oral sites (upper vestibule, lower vestibule, and hard palate) represent an innovative cell source for maxillo‐facial tissue engineering applications in terms of accessibility and self‐commitment towards osteogenic lineage. Periosteal cells (PCs) were isolated from patients with different ages (20–30 yy, 40–50 yy, 50–60 yy); we then analyzed the in vitro proliferation capacity and the bone self‐commitment of cell clones culturing them without any osteogenic supplement to support their differentiation. We found that oral PCs, independently of their origin and age of patients, are mesenchymal stem cells with stem cell characteristics (clonogenical and proliferative activity) and that, even in absence of any osteogenic induction, they undertake the osteoblast lineage after 45 days of culture. These results suggest that oral periosteal cells could replace mesenchymal cells from bone marrow in oral tissue‐engineering applications. J. Cell. Physiol. 231: 607–612, 2016. © 2015 Wiley Periodicals, Inc.